Letter to the Editor regarding the article: “Burnout in Portuguese Healthcare Professionals: An Analysis at the National Level“ by João Marôco, Ana Lúcia Marôco, Ema Leite, Cristina Bastos, Maria José Vazão, Juliana Campos. Acta Med Port 2016;29:24-30. - Gama Marques, João (2016)
Keywords: Burnout, Professional; Health Personnel; Portugal.